ON AN EXPANSION FORMULA FOR THE MULTIVARIABLE -FUNCTION INVOLVING GENERALIZED LEGENDRE’S ASSOCIATED FUNCTION - Singh, Yashwant; Kumar Mandia, Harmendra (International Journal of Research -GRANTHAALAYAH, 2016)
The authors have established a new expansion formula for multivariable -function due to Prasad [5] in terms of products of the multivariable -function and the generalized Legendre’s associated function due to Meulenbeld [3]. Some special cases are given in the last.